Income tax flattening: does it help to reduce the shadow economy? - Klara Sabirianova Peter (Institute for the Study of Labor (IZA), 2009)
This paper examines the effect of global transition to simpler, flatter income tax systems on the size of the shadow economy. By offering a new estimation framework, the paper revives the traditional electricity consumption approach to measuring the shadow economy. It overcomes the limitations of previous literature by using a new functional form, better quality data, a larger sample of 170 countries, a longer time span of 25 years, a panel framework, and instrumental variables. Our analysis provides strong evidence of a positive relationship between income tax rates and the size of the shadow economy. The effects of structural progressivity and complexity of national tax schedules are also found to be positive and statistically significant. These positive effects are reinforced when tax changes are accompanied by improving government services and strengthening the legal system. The flat tax is estimated to reduce the shadow economy in the short run, but this effect diminishes and disappears in the long run.
urn:nbn:de:101:1-2009062240
Keywords: D73; H1; J3; J4; O1; P2; 330; Shadow economy; tax evasion; personal income tax; corporate income tax; flat tax; structural progressivity; tax complexity; electricity approach; institutions; Steuerreform; Flat Tax; Wirkungsanalyse; Schattenwirtschaft; Welt